2014
DOI: 10.1016/j.jval.2014.08.1661
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Treating Thalassemia In Greece

Abstract: was calculated. Considering a switch to aztreonam lysine, the reduction of exacerbation was estimated in order to maintain the overall treatment cost. For the base case, ex-factory prices were considered; for sensitivity analysis, discounts ranged from 15 to 50%. Results: Switching to aztreonam lysine would not increase overall treatment costs in 8/12 options; even maintaining current exacerbation episodes could lead to SNS savings. In the remaining options, the required reduction of exacerbations varies depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
5
2
Order By: Relevance
“…The study findings revealed that the total direct medical costs per TDT patient per year were AED 131,156 (USD 35,710) (USD 1 = AED 3.67), of which ICT was the most expensive cost component (59.8%), followed by blood transfusions (26.1%). The findings of this study have shown that the annual mean direct medical cost is in agreement with that found in other studies conducted in Western countries, such as Greece (EUR 32,054) [23] and Italy (EUR 31,883) [13], but lower than that found in studies conducted in the United States (USD 43,969 and USD 128,969) [16,29]. Contrarily, our estimates are higher than those reported in middle-and lowincome countries such as Turkey (USD 14,360) [12], Thailand (USD 563) [15], India (USD 1135) [31], and Iran (EUR 1,731) [24] (USD 7,287) [14].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The study findings revealed that the total direct medical costs per TDT patient per year were AED 131,156 (USD 35,710) (USD 1 = AED 3.67), of which ICT was the most expensive cost component (59.8%), followed by blood transfusions (26.1%). The findings of this study have shown that the annual mean direct medical cost is in agreement with that found in other studies conducted in Western countries, such as Greece (EUR 32,054) [23] and Italy (EUR 31,883) [13], but lower than that found in studies conducted in the United States (USD 43,969 and USD 128,969) [16,29]. Contrarily, our estimates are higher than those reported in middle-and lowincome countries such as Turkey (USD 14,360) [12], Thailand (USD 563) [15], India (USD 1135) [31], and Iran (EUR 1,731) [24] (USD 7,287) [14].…”
Section: Discussionsupporting
confidence: 92%
“…Patients treated with DFO had a significantly lower number of blood transfusion units than those treated with other ICTs. Contrastingly, another study showed that DFX reduced blood transfusion volume in relation to DFO [ 23 ]. This difference could be explained by the difference of sex in patients treated with DFO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United Kingdom, total healthcare expenditure attributable to managing β‐thalassemia major over 50 years was estimated to be USD 720 201 at 2013‐2014 prices 78 . A study of 331 patients with β‐thalassemia in Greece found that the mean annual cost per patient, including all treatment strategies, was EUR 32 064 for the period 2009 to 2011, a value that increased from EUR 30 997 in 2009 to EUR 32 564 in 2011 79 . In Iran, a study of the economic burden of β‐thalassemia major found that the average annual cost per patient was USD 8321.80, regardless of the cost of lost welfare 80 .…”
Section: Factors Affecting Incidence and Prevalence In Different Counmentioning
confidence: 99%